Diseño de un sistema administrativo, contable y financiero de la panificadora "El Relampago" ubicada el la Colmena de la Ciudad de Quito. - Moreno Bautista, José Luis (2013)
The design of an administrative, accounting and financial system for the bakery aims to maximize and optimize all processes through good management maximizing all its resources and to assist management decisions in a timely manner. It will include an organic functional manual rules, policy manual, manual of procedures, internal control policies, methods of documentation and financial indicators.